Dynamics of Qur’anic and Hadith Studies in the Digital Age: A Literature Review of the Application of Technology in Islamic Education - Siregar, Kardina Engelina (Proceedings of International Conference on Muslim Society and Thought, 2024)
The development of digital technology is changing Islamic education. This study aims to conduct a literature review on the dynamics of Qur’an and Hadith studies in the digital era, with an emphasis on the application of technology in the Islamic education curriculum. Using a literature study approach, we investigate the evolution, trends, challenges, and opportunities that arise with respect to the application of technology in Islamic education. The results of the review show that digital technology has changed the way people read the Qur’an and Hadith, increased learning efficiency, expanded the scope of Islamic education, and allowed wider access to religious resources. However, issues such as the quality of digital content, concerns about the veracity of sources, and limitations in access to technology also need to be addressed. This research provides valuable insights for building an Islamic education curriculum that is responsive to the digital age. The research also shows how important it is to combine technology with traditional methods for studying the Qur’an and Hadith.